History and impact of Indian dubbed into Arabic movie channel "Bollywood": Exploratory study - Omar, Yara Ayman Yosry (AUC Knowledge Fountain, 2015)
This study explores the cultural impact of Indian dubbed into Arabic movies on the knowledge of the Egyptian audience towards the Indian culture. The main channels chosen to conduct this study were MBC Bollywood, Fox, Zee Aflam and Dubai One. The main theoretical framework applied in relation to this study is the Hybridity theory alongside with the term “Glocalization”. The two main methodologies used to test out this exploratory study were Qualitative content analysis aiming to discover the main aspects of the Indian culture portrayed in the Indian dubbed into Arabic movies. The result supported the same aspects mentioned in the literature review, which were color, dance, music, and love stories. Through those characteristics, quantitative surveys were distributed to measure the level of knowledge, attitudes, perception and interest towards the Indian culture. Findings showed that nearly 77% of the audience became more interested in Indian movies more than before. The audience who watch more Indian dubbed into Arabic movies proved to have the most positive attitude and most knowledge and relation to the Indian culture.